2019
DOI: 10.5114/cipp.2019.88276
|View full text |Cite
|
Sign up to set email alerts
|

Shyness, self-presentation, adonization, and influence tactics in close relationships

Abstract: Empirical research reveals the difficulties that shy people must face as part of their social functioning and attaches a pejorative connotation to shyness in the process of establishing and maintaining interpersonal relations. The purpose of the study was to investigate certain aspects of social functioning of shy people: the preferred self-presentation styles, readiness to adopt adonization and influence tactics in intimate relationships. participants and procedure The study was performed on a group of 234 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Other authors [ 45 , 81 ] showed that shy people tend to employ a protective self-presentational style since they prefer to avoid social disapproval rather than to achieve others’ approval. Mandal and Wierzchoń [ 82 ] revealed that shy individuals are inclined to adopt self-deprecation more often than their less shy counterparts. Simultaneously, non-shy people use self-promotion more frequently than their shy peers.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors [ 45 , 81 ] showed that shy people tend to employ a protective self-presentational style since they prefer to avoid social disapproval rather than to achieve others’ approval. Mandal and Wierzchoń [ 82 ] revealed that shy individuals are inclined to adopt self-deprecation more often than their less shy counterparts. Simultaneously, non-shy people use self-promotion more frequently than their shy peers.…”
Section: Discussionmentioning
confidence: 99%
“…meaSureS Shyness. Shyness was assessed using the Revised Cheek and Buss Shyness Scale (RCBS; Hopko et al, 2005;Polish version: Kwiatkowska et al, 2016;Mandal & Wierzchoń, 2019). The RCBS consists of 13 statements (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Shy persons have a tendency for negative affect and nonconstructive ways of coping with one's own emotionality (Eisenberg et al, 1995). Shyness correlates with defensive styles of self-presentation (Bober et al, 2022;Mandal & Wierzchoń, 2019;Schlenker & Leary, 1982), low influence skills (Ericsson, 2018), and Internet addiction (Li et al, 2023), and implies lower relationship satisfaction (Baker & McNulty, 2010;Rowsell & Coplan, 2013).…”
Section: Shynessmentioning
confidence: 99%